Development and Optimization of Cocoa-Based Herbal Face Pack Using Design of Experiments - Devadiga, Rashmitha Rama; Sadeeksha; Reeha; Rohan; Madhava, Ashwini (International Journal of Pharmaceutical Investigation, 2025)
Background Skincare products featuring natural ingredients are widely favored for their perceived efficacy and safety. This study aimed to develop and evaluate cocoa fruit-based formulations for skincare, enriched with synergistic herbal constituents such as rose petals, guava peel and papaya leaf. Materials and Methods The cocoa fruit underwent processing and fermentation to yield cocoa beans. In this study, 12 facial pack formulations were developed using JMP 17 software, with variations in the quantities of cocoa powder, papaya leaf powder, guava peel powder and rose petal powder. The custom design generated by JMP facilitated the creation of optimized formulations, considering responses such as bulk density and angle of repose. The final optimized formulation was assessed for organoleptic properties, moisture content, washability, bulk density, angle of repose, total ash value and phytochemical constituents. Results Optimal formulations were determined for the product based on desired attributes and skincare benefits. The DoE-generated twelve facial pack formulations exhibited acceptable model fit, with the optimized formulation demonstrating positive outcomes in organoleptic and phytochemical analyses. Conclusion This study successfully formulated skincare products using cocoa bean and herbal constituents, demonstrating their potential for natural skincare formulations with desirable properties and therapeutic benefits. DoE enabled a data-driven approach to optimize the herbal facial pack formulation efficiently, ensuring robust physical properties and potential skincare benefits. Future research endeavors could focus on further refining formulations and exploring additional applications in skincare product development.
Keywords: Herbal face pack; Jmp pro-18; Optimization; Theobroma cacao